(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
The article proposes to consider the definition of character in literary criticism. On the material of V. Faschenko’s work an attempt is made to orient research views on the role of characterization in fiction. The analysis involves neo-realist novels "Saldаtiki!" by V. Vynnychenko and "Third Revolution" by V. Podmohilin.